Influence of Modulating Loss Power on Reactive Properties of Electronic Flow in Resonant Generators - V. K. Morоz; A. A. Polischuk; G. A. Mikhaltsevich; E. M. Satsukevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
It is shown that modulating loses significantly influence on resonant properties of generators